THE IMPACT EVALUATION OF THE BASE TRANSCEIVER STATION (BTS) UNIVERSAL SERVICE OBLIGATION (USO) PROJECT IN THE REMOTE, FRONTIER, AND OUTERMOST (3T) AREA ON BRIDGING INDONESIA’S DIGITAL DIVIDE USING DIFFERENCE-IN-DIFFERENCE MODEL - Priska Apnitami; Gunawan Wibisono (BPSDMP Kominfo Jakarta, 2023)
With the Base Transceiver Station (BTS) Universal Service Obligation (USO) project in the remote, frontier, and outermost (3T) region, the Indonesia government seeks to encourage equitable distribution of information and communication technology (ICT) infrastructure throughout the country in order to bridge the digital divide. This study tries to see the impact of BTS USO in 134 districts/cities in the 3T region in bridging Indonesia's digital divide represented by internet penetration using an econometric approach with a Difference-in-Difference (DiD) model using data from 2015 as before program data and data from 2020 as after program data. From the obtained results, a significant impact of the BTS USO on internet penetration across the 3T regions has not been found. One of the possibilities is that up until early March 2020, only 134 districts/cities already had BTS/USO whereas 34 districts/cities only had USO BTS below 10 units. Based on the results of this study, there are several policy recommendations that can be taken, including increasing equal distribution of ICT infrastructure, equalizing formal education, increasing digital literacy in the 3T regions, and providing cellular service subsidies to residents.